Data Associated with "The Key Role of Cloud-Climate Coupling in Extratropical Sea Surface Temperature Variability" - Boehm, Chloe; Thompson, David W.J. (Colorado State University. Libraries, 2021)
Cloud radiative effects have long been known to play a key role in governing the mean climate. In recent years, it has become clear that they also contribute to climate variability in the tropics. Here we build on recent work and probe the role of cloud radiative effects in extratropical sea-surface temperature (SST) variability. The impact of cloud radiative effects on climate variability is explored in ‘cloud-locking’ simulations run on an Earth System Model. The method involves comparing the output from two climate simulations: one in which clouds are coupled to the atmospheric circulation and another in which clouds are prescribed and thus decoupled from the flow. The results reveal that coupling between cloud radiative effects and the atmospheric circulation leads to widespread increases in the amplitudes of extratropical SST variability from monthly to decadal timescales. Notably, the amplitude of monthly to decadal variability over both the North Atlantic and North Pacific oceans is between ~25-40% larger when clouds are coupled to the circulation. The increases are consistent with the ‘reddening’ of cloud shortwave radiative effects that arises when clouds interact with the large-scale circulation. The results suggest that a notable fraction of observed Northern Hemisphere sea-surface temperature variability - including that associated with North Pacific and North Atlantic decadal variability - is due to cloud-circulation coupling.
Boehm_and_Thompson_CloudLocking_2021_Data.zip contains 12 NetCDF files. Each data file contains output data from simulations run on the Max Planck Institute Earth System Model. Each file has the output for a single variable and three dimensions: time, latitude and longitude.
Department of Atmospheric Science